ANALYSIS OF THE RELATIONSHIP BETWEEN ECONOMIC VALUE ADDED AND MARKET VALUE ADDED - Kristína Jančovičová BOGNÁROVÁ (Challenges of the Knowledge Society)
Economic Value Added (EVA) is one of the most important modern performance measures. The main difference between EVA and traditional measures is that EVA incorporates both financing costs of debt and equity capital. In addition, EVA includes adjustments that minimize some accounting distortions. EVA and Market Value Added (MVA) provide a more accurate evaluation of the firm’s financial performance. This paper involves a case study that analysis the use of EVA in selected Slovak companies. It examines the incremental information of a set of performance measures in the time period of 2010 - 2015, using regression models. Furthermore, we analyse the MVA performance and the relationship between EVA and MVA.